Sublethal Effects of Methanolic Extract of Raphia hookeri on the Reproductive Capacity of Clarias gariepinus. (5th November 2014) - Afolayan, Adedotun O.; Borokini, Temitope I.; Afolayan, Gloria O.
Abstract : Raphia hookeri fruits are used for fishing in Nigeria due to their ichthyotoxic properties. This study investigated the toxic effects of R. hookeri on the reproductive capacity of Clarias gariepinus . The results from both short-term (96-hour test) and long-term (3-month sublethal test) bioassays revealed a linear relationship between R. hookeri extract dose and negative effects on the catfish. The percentage survival of both sexes of the catfish decreased with increasing extract concentration at short-term exposure, with LC50 values of 600 mg/L and 800 mg/L for male and female, respectively. At long-term exposure, the reproductive capacity of 10–12-month-old male and female brood-stocks diminished at relatively higher concentrations of R. hookeri fruit extract, with the gravid females producing fewer and mostly unviable eggs. The fruit extract also affected the eggs' hatchability and fry survival when the exposed gravid females were treated with pituitary hormone and sperms from unexposed males, while the exposed males were unable to sexually stimulate female brooders. Sperms and pituitary hormone from exposed males were infertile, leading to low percentage of hatched eggs and mortality of the few hatched fries within 24 hours. These results confirmed the ethnobotanical use of this fruit extract for fishing in Nigeria.